Review of Nasuconia Sakakibara, 2006 (Hemiptera: Membracidae) with description of three new species - Gonzalez-Mozo, Laura C.; Ware, Jessica L. (Zootaxa, 2023)
The treehopper genus Nasuconia Sakakibara, 2006 previously included four species and was recorded only from Brazil. Here we provide a revised diagnosis of the genus and describe three new species: Nasuconia ellenfutterae sp. nov. from Ecuador, Nasuconia guianensis sp. nov. from French Guiana and Nasuconia yasuni sp. nov. from Ecuador. The genus can be distinguished by the following combination of characters: frontoclypeus conical with transverse grooves, obliquely projected forward at least 1/3 of its length beyond suprantennal margin; pronotum navicular, low, punctate, with longitudinal elevated lines or nodes; first valvulae with ventral interlocking device distinctively sinuate. Two informal species groups are recognized based on characters of the head, forewing and leg chaetotaxy. A key to species, photographs, updated morphological descriptions, and the first descriptions of the female and male genitalia of Nasuconia species are provided. Comparisons of cucullate setae and fine abdominal integument structures are also made using scanning electron microscopy.